Innovation of Blockchain For Controlling Prescription Drug Abuse; a Case Study of Puskesmas in Palopo City - Riska Yuli Nurvianthi; Aisyah Warsid (Universitas Pahlawan Tuanku Tambusai, 2025)
Prescription drug management and oversight are critical to ensuring the effectiveness of pharmacy management in healthcare settings. In community health centers, challenges such as lack of transparency in drug distribution, reliance on error-prone manual record-keeping, and poor integration with digital systems hinder effective pharmaceutical management. This study explores the application of blockchain technology in pharmaceutical management, focusing on enhancing transparency, improving drug distribution efficiency, and ensuring compliance with pharmaceutical regulations. A mixed-methods approach combining survey analysis and participant observation was employed. Data were collected from health workers and patients through surveys conducted before and after blockchain implementation. Additionally, in-depth interviews with pharmacists and health workers were conducted, and direct observations of drug distribution processes and electronic record-keeping were performed. Blockchain implementation led to a significant 85% improvement in drug monitoring effectiveness, an 82% increase in drug distribution transparency, and a 40% reduction in prescription errors. The technology also enabled the detection of counterfeit prescriptions and optimized the pharmaceutical supply chain. Blockchain technology significantly improves pharmaceutical management by enhancing supply chain efficiency, increasing transparency in drug distribution, and ensuring compliance with pharmaceutical regulations. Further research is needed to evaluate its cost-effectiveness and assess health systems' readiness for wider integration of blockchain technology.